Kedudukan dan Kewenangan Dewan Pertimbangan Presiden dalam Tinjauan Fiqh Siyasah - MOCHAMMAD FAISHOL (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2019)
This paper aims to find out the perspective of Fiqh Siyasah on the position and authority of the Presidential Advisory Council (Watimpres) under Constitutional Law in Indonesia. From the results of this study, it can be concluded that the Presidential Advisory Council is domiciled in the office of the President because it is part of the power vested on the state government and is responsible to the President. Presidential Advisory Council is authorized to provide advice and consideration to the President, whether requested or not. Every member of the Presidential Advisory Council can give advice and consideration to the President. Watimpres is not permitted to provide information, statements, and/or disseminate the contents of advice and consideration to any party. In the QS. Ali Imran (3): 104 implicitly outlines the existence of an advisory body in the community. Ahl al-Halli wa al-’Aqdi is not under the caliphate and is accountable for the caliph. The responsibility to give advice and consideration to the President based on the Islamic notion of amar ma'ruf nahi munkar comes under the QS. Ali Imran (2): 104, 110, and 114. Besides, the Prophet Muhammad has ordered to convey the truth even though it was bitter for those who delivered it.